2018
DOI: 10.1101/440826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ghr-miR164 and GhNAC100 module participates in cotton plant defence against Verticillium dahliae

Abstract: Previous reports have shown that many miRNAs were identified at the early induction stage during which Verticillium dahliae localizes at the root surface. In this study, we constructed two sRNA libraries of cotton root responses to this fungus at the later induction stage when the pathogen enters the root vascular tissue. We identified 71 known miRNAs and 378 novel miRNAs from two pathogen-induced sRNAs and the control libraries. Combined with degradome and sRNA sequencing, 178 corresponding miRNA target genes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The hlu-miR164b cleavage site within the transcript of hops NAC domain-containing protein was con rmed by 5' RLM-RACE analysis done by Mishra, et al [53]. Hu, et al [61] observed a signi cant decrease of ghr-miR164 in the response of cotton plants to infection with V. dahliae. Additionally, the researchers showed that ghr-miR164 directly cleaves the mRNA of GhNAC100, and silencing of ghr-miR164 leads to increased GhNAC100 expression, which in turn increases plant resistance to the fungus.…”
Section: Discussionmentioning
confidence: 92%
“…The hlu-miR164b cleavage site within the transcript of hops NAC domain-containing protein was con rmed by 5' RLM-RACE analysis done by Mishra, et al [53]. Hu, et al [61] observed a signi cant decrease of ghr-miR164 in the response of cotton plants to infection with V. dahliae. Additionally, the researchers showed that ghr-miR164 directly cleaves the mRNA of GhNAC100, and silencing of ghr-miR164 leads to increased GhNAC100 expression, which in turn increases plant resistance to the fungus.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous database, ghr-miR397 was identified to regulate 6 target genes namely Gh_A03G0417, Gh_D03G1128, Gh_A03G2084, Gh_D13G2373, Gh_A13G2215 and Gh_D13G2524, out of which, Gh_A03G0417 and Gh_D03G1128 showed remarkable upregulation expression under V. dahliae treatment ( Supplementary Figure 3 ) and located on the A and D subgenomes of G. hirsutum ( Hu et al, 2020b ). Therefore, two target genes were suffered to further research.…”
Section: Resultsmentioning
confidence: 99%
“…The GUS transient expression in the tobacco leaves, histochemical staining and activity quantified was performed as described by Hu et al (2020b) . In brief, the leaves were placed in pre-cooled 95% acetone on ice overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In response to infection with V. nonalfalfae, the resistant cultivar showed signi cantly lower expression of hlu-miR164b, which targets transcripts of NAC domain-containing proteins. Chen, Peng, Yang and Wu [66] observed a signi cant decrease of ghr-miR164 in the response of cotton plants to infection with V. dahliae. Additionally, the researchers showed that ghr-miR164 directly cleaves the mRNA of GhNAC100, which in turn increased the resistance of plants to the fungus.…”
Section: Discussionmentioning
confidence: 96%